Getting by in New York City: Bonding, Bridging and Linking Capital in Poverty–Impacted Neighborhoods. (March 2019) - Lukasiewicz, Karolina; Bahar, Ozge Sensoy; Ali, Samira; Gopalan, Priya; Parker, Gary; Hawkins, Robert; McKay, Mary; Walker, Robert
A lack or low level of social capital is associated with negative outcomes for communities impacted by poverty. However, less is known about how different types of social capital operate on the ground in poverty–impacted urban neighborhoods. This article explores the ways in which bonding, bridging, and linking capital manifest among residents of two poverty–impacted neighborhoods in New York City. Findings of the study reveal that urban neighborhood characteristics, more than individual–level factors, compromise the ability to develop and utilize the leveraging role of bridging and linking capital. Lack of safety resulted in limited trust, and involvement in community life limit bonding capital. Opportunities for bridging are restricted by the socioeconomically homogenous and spatially segregated nature of the communities. Linking capital is undermined by the lack of resources in the neighborhoods. These structural barriers prevent communities from breaking the cycle of poverty and should be explicitly targeted when developing interventions focused on building social capital.